Fuzzy Based Spam Filtering - M. Hameed, Sarab (Iraqi Journal of Science, 2023)
Emails have proliferated in our ever-increasing communication, collaboration andinformation sharing. Unfortunately, one of the main abuses lacking complete benefits ofthis service is email spam (or shortly spam). Spam can easily bewilder system becauseof its availability and duplication, deceiving solicitations to obtain private information.The research community has shown an increasing interest to set up, adapt, maintain andtune several spam filtering techniques for dealing with emails and identifying spam andexclude it automatically without the interference of the email user. The contribution ofthis paper is twofold. Firstly, to present how spam filtering methodology can beconstructed based on the concept of fuzziness mean, particularly, fuzzy c-means (FCM)algorithm. Secondly, to show how can the performance of the proposed FCM spamfiltering approach (coined hence after as FSF) be improved. Experimental results oncorpora dataset point out the ability of the proposed FSF when compared with the knownNaïve Bayes filtering technique.